Implications on the Pb bioaccumulation and metallothionein levels due to dietary and waterborne exposures: The Callinectes danae case - Bordon, Isabella C. [UNESP]; Emerenciano, Andrews Krupinski; Melo, Julia Reali Costa; Silva, José Roberto Machado Cunha da; Favaro, Deborah Inês Teixeira; Gusso-Choueri, Paloma Kachel [UNESP]; Campos, Bruno Galvão de [UNESP]; Abessa, Denis Moledo de Souza [UNESP] (Elsevier, 2018)
This study aimed to assess the bioaccumulation of Pb and induction of metallothionein-like proteins (MT) in Callinectes danae through single and combined dietary and waterborne exposures. Male C. danae individuals were collected in the south area of the Cananéia-Iguape-Peruíbe Protected Area (APA-CIP), in São Paulo State, Brazil. After an acclimatization period, exposure assays were performed during 7 and 14 days, at two Pb concentrations (0.5 e 2.0 µg/g) in 4 treatments: 1) control; 2) contaminated water only; 3) contaminated food only; 4) contaminated water and food. The results indicate that C. danae is highly tolerant to Pb exposure at the evaluated concentrations. In gills, Pb bioaccumulation is more dependent of water efflux and time of exposure (higher Pb values). However, pathways act simultaneously in the induction of MT expression in this tissue. The decreases in Pb accumulation in the combined treatments and MT increases after 14 days in gills suggests that these proteins play a detoxification function in the presence of Pb. In hepatopancreas, depending on the predominance of a certain pathway or combined pathways, accumulation occured at different times. For muscle tissue, bioaccumulation was observed due to contaminated water exposure, but not dietary exposure, probably because Pb concentrations were low.
Keywords: Artificial food; Bioaccumulation; Biomarkers; Blue crabs; Metallothionein-like proteins; Metals